Internalisasi Karakter Qur’ani Melalui Bimbingan Siswa Sekolah Dasar - Hamdi, Edi; Hermatasiyah, Nur; Muttaqin, Muhammad Fauzan (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
The aim of the research is to strengthen Qur'anic character through guidance and counseling for students in elementary schools. The research method uses a qualitative approach to phenomenological studies in elementary schools based on the Koran in daily life. Data collection uses observation instruments, interviews, documentation studies of school programs related to Qur'anic characters. Validation is applied using triangulation techniques. The data analysis used is interactive model analysis with data collection, reduction, data display and verification. The results of the research explain that teachers' efforts to internalize Qur'anic characters through guidance and counseling are carried out individually and classically. Individually, in the form of instructions to students to understand the Al-Qur'an by reciting it, reading, studying, practicing and teaching it. Classically through tahfidz, teacher example, students' Qur'anic character habituation programs.